Pengaruh profitabilitas, cash holding, ukuran perusahaan terhadap manajemen laba dengan kepemilikan manajerial sebagai variabel moderasi - Ela Rosiana; Wukuf Dilvan Rafa; Elok Heniwati (LPMP Imperium, 2024)
This research was carried out with the aim of testing and analyzing the influence of profitability, cash holding, and firm size on earnings management through moderating managerial ownership. The type of research applied is causal based and involves quantitative methods from secondary data. The population of this study consists of companies in the real estate, property and building construction sectors that are officially listed on the IDX for the 2020-2023 period. Purposive sampling technique is a data collection technique. Data processing involves the Eviews version 10 application. Sample selection. Profitability has a positive influence on earnings management, cash holding does not affect earnings management, and company size does not affect earnings management. Meanwhile, managerial ownership cannot moderate profitability in earnings management, cash holding with earnings management can be moderated by managerial ownership, and company size in earnings management cannot be moderated by managerial ownership.